Webinar Sosialisasi di SDN 1 Munjuljaya Guna Menumbuhkan Rasa Minat Baca Anak di Rumah - Ghea Sandra Pratiwi; Shareefa Amalia; Annida Misyika; Ayes Yesti Amalia; Farida Amalia; Fariha Nurul Izzah; Erna Suwangsih (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
Indonesia is ranked 74th in the reading ability category based on the results of the 2018 PISA survey. The low reading interest in students is the government's focus to continue working to increase reading interest, one of which is reading activities for 15 minutes before learning activities at school. However, due to COVID-19 and government policies, learning was carried out remotely or at home. PJJ is also implemented in SDN 1 Munjuljaya, Purwakarta District, Purwakarta Regency, which means reading activities for 15 minutes, visits to libraries, reading corners are stopped. To foster a stopped reading interest, community service is carried out, which aims to provide education, especially for parents of students, whose role is to foster children's reading interest at home. The results obtained from this service turned out to be very beneficial for teachers and parents; in particular, they became more aware of increasing children's reading interest at home.